Education to Strengthen the Economy of the Utilization of Aren Nira Producing Bioetanol in Lonuo Village, Bone Bolango District - Hasanuddin; Taan, Hapsawati; Mardin, Herinda; Salimi, Yuszda K.; Rahmatia; Arafat, Muhammad Yasser; Larosa, Esta; Rasyid, Abdul; Ashari, Sri Ayu (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
This economic education activity for palm sap farmers aims to provide economic strengthening and build awareness among the public, especially palm sap farmers, that palm sap water can be utilized and made into several products with high economic value, for example bioethanol products. Apart from that, it can also minimize the negative impact of the production of alcoholic drinks made from palm sap in Lonuo village. This activity uses educational methods, socialization and community assistance for sugar palm sap farmers. Empowering sugar palm farmers through product diversification is the key to increasing the quality and quantity of sugar palm sap products into various marketable products such as bioethanol. This economic education activity for palm sap farmers has had a positive impact and response from the Lonuo village community. This can be seen from the enthusiasm of the community in participating in activities at the village office. The community received education well and smoothly and increased public understanding regarding the use of palm sap into products of high economic value such as bioethanol.